The Effect of Job Rewards and Organizational Commitment on Organizational Citizenship Behavior through Mediation of Perceived Organizational Support and Work Engagement in Private Higher Education Lecturers: A Conceptual Framework - Tawil, Muhammad Risal (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This paper is motivated by the fact that there are still many lecturers at private universities who do not have the sincerity in pursuing a career even though there are many opportunities and government regulations in favor of lecturer development efforts. The existence of lecturers in universities is very vital, considering that the dharma of universities as a whole is carried out by lecturers. Besides, the performance measure of a university is also largely determined by the quality of the lecturers at the university. But in reality there are still many lecturers who are not serious in pursuing a career in higher education, especially in private universities. This paper will review what factors can encourage the improvement of organizational citizenship behavior of lecturers at private universities. Based on these problems, the authors attempted to elaborate and analyze the effect of job rewards and organizational commitment on organizational citizenship behavior by strengthening perceived organizational support and work engagement. It is hoped that this paper can provide information about the factors that can encourage the improvement of organizational citizenship behavior, especially for lecturers at private universities.